Penerapan Problem-Based Learning Berbasis Deep Learning Untuk Meningkatkan Keaktifan Belajar Siswa SD - Ismoyowati Ismoyowati; Sulistyo Sulistyo; Onik Farida Ni'matullah (LPPM Institut Pendidikan Nusantara Global, 2026)
The low level of student engagement in Integrated Science (IPAS) learning at the elementary school level indicates the need for instructional approaches that foster deep cognitive and social involvement. This study aims to examine the effect of implementing a Deep Learning approach through the Problem-Based Learning (PBL) model on the learning engagement of fifth-grade students. This research employed a quantitative approach with a quasi-experimental design, specifically a pretest–posttest nonequivalent control group design. The participants consisted of 27 students in the experimental group and 28 students in the control group. Data were collected using a student engagement observation sheet and analyzed using Analysis of Covariance (ANCOVA). The results revealed a significant difference in student engagement between the experimental and control groups after controlling for initial ability (p < 0.001), with an effect size of η² = 0.275, which falls into the large category. These findings indicate that the implementation of a Deep Learning approach through the PBL model is effective in enhancing elementary students’ engagement in IPAS learning. Therefore, this approach can serve as a relevant instructional strategy alternative in the implementation of the Merdeka Curriculum.